Juridical Analysis of First-Level Health Facility Regulations in BPJS Kesehatan - R.Firmansyah; S.Gunardi (International Medical Journal Corp. Ltd, 2024)
Introduction: The Indonesian National Health Insurance program, managed by BPJS Kesehatan, relies heavily on First-Level Health Facilities (FKTP) as the primary gatekeeper for public healthcare. However, inconsistencies within the regulatory frameworks governing FKTP operations frequently lead to implementation disparities and limited legal certainty for both providers and beneficiaries. Methods: This study employs a normative juridical research methodology, utilizing a statutory, conceptual, and analytical approach to evaluate the coherence of prevailing health regulations and presidential decrees governing primary care. Results: The analysis reveals distinct regulatory friction between the operational mandates issued by BPJS Kesehatan and the clinical autonomy standards established by the Ministry of Health. Overlapping authorities regarding accreditation, capitation fund distribution, and performance-based contracting have created bureaucratic inefficiencies that undermine service delivery. Discussion: By exploring the literature on administrative law and public health governance, the discussion highlights a structural disconnect between macro-level national health policies and the micro-level implementation guidelines enforced upon primary providers. This legal gap compromises the standard of care and exposes healthcare professionals to unnecessary regulatory vulnerabilities. Conclusions: To resolve these systemic conflicts, the government must harmonize secondary legislation, precisely delineate the supervisory boundaries between BPJS Kesehatan and regional health offices, and establish a unified legal framework that balances financial efficiency with quality medical service.